Interleukin-37 Inhibits Colon Carcinogensis During Chronic Colitis - Mountford, Steffeni; Ringleb, Andrea; Schwaiger, Rahel; Mayr, Doris; Kobold, Sebastian; Dinarello, Charles A.; Bufler, Philip (Frontiers in Immunology, 2019)
Inflammatory bowel disease increases the risk of developing colon cancer. Interleukin (IL-) 37 is a fundamental inhibitor of innate immunity by reducing systemic and local inflammation. IL-37 protein is expressed in healthy and diseased bowel and liver tissue. Here, we tested whether transgenic expression of human IL-37 protects IL-10 deficient (IL-10KO) mice from chronic colitis. IL-37tg mice were crossbred with IL-10KO mice. Homozygous IL-10KO/IL-37tg and IL10KO drank 2 % dextran sulphate sodium (DSS) in water for 5 days to induce mild colitis. Colon carcinogenesis was triggered by intragastric administration of celecoxib. Endpoints were clinical parameters of colitis, cytokine responses in LPS-stimulated whole blood and explanted colon specimen and qPCR analysis of colon biopsies. Colon inflammation and number of adenoma - carcinoma were analyzed by histology. During the DSS-induction phase IL-10KO and IL-10KO/IL-37tg mice had a similar weight loss due to mild acute colitis. From day 115 there was a significantly improved weight gain in IL-10KO/IL37-tg mice, though colon length was similar. After ex vivo LPS stimulation whole blood of IL-10KO/IL-37tg compared to IL-10KO mice released less IL-6, IL-17, IFNγ and TNFα and ex vivo colon cultures showed reduced IL-6 production both indicative of reduced inflammatory conditions under the influence of IL-37. 6 out of 10 IL-10KO mice developed colon adenoma and carcinoma. Only one adenoma but no carcinoma was detected in colons of IL-10KO/IL-37tg mice. In conclusion, IL-37 transgene expression protects IL-10KO mice from colon carcinogenesis. It remains unclear whether IL-37 has direct tumor suppressing properties.